Effect of Celastrol on LncRNAs and mRNAs Profiles of Cerebral Ischemia-Reperfusion Injury in Transient Middle Cerebral Artery Occlusion Mice Model - Liu, Jiandong; Guo, Xiangna; Yang, Lu; Tao, Tao; Cao, Jun; Hong, Zexuan; Zeng, Fanning; Lu, Yitian; Lin, Chunshui; Qin, Zaisheng (Frontiers in Neuroscience, 2022)
Celastrol plays a significant role in cerebral ischemia-reperfusion injury. Although previous studies have confirmed that celastrol post-treatment has a protective effect on ischemic stroke, the therapeutic effect of celastrol on ischemic stroke and the underlying molecular mechanism remain unclear. In the present study, focal transient cerebral ischemia was induced by transient middle cerebral artery occlusion (tMCAO) in mice and celastrol was administered immediately after reperfusion. We performed lncRNA and mRNA analysis in the ischemic hemisphere of adult mice with celastrol post-treatment through RNA-Sequencing (RNA-Seq). A total of 50 differentially expressed lncRNAs (DElncRNAs) and 696 differentially expressed mRNAs (DEmRNAs) were identified between the sham and tMCAO group, and a total of 544 DElncRNAs and 324 DEmRNAs were identified between the tMCAO and tMCAO+celastrol group. Bioinformatic analysis was done on the identified deregulated genes through gene ontology (GO) analysis, KEGG pathway analysis and network analysis. Pathway analysis indicated that inflammation-related signaling pathways played vital roles in the treatment of ischemic stroke by celastrol. 4 DElncRNAs and 5 DEmRNAs were selected for further validation by qRT-PCR in brain tissue, primary neuron, astrocyte and BV2 cells. The expression of 5830444B04Rik, C030005K06Rik, Elavl4, Sh3bp4, HIF-1α, Ascl2 and Acod1 in brain tissue showed the same fold change patterns as those in the RNA-Seq results, but changes in 4930413F20Rik and Gm15444 were not statistically significant in the RNA-Seq results. Our study suggests celastrol treatment can effectively reduce cerebral ischemia-reperfusion injury. The bioinformatics analysis of profile of lnRNAs and mRNAs in ischemic hemisphere of adult mice provide a new perspective in the neuroprotective effects of celastrol, particularly with regards to ischemic stroke.